Development of Communication and Creativity Competency Assessment Instruments in The Chempreneurship Course - Mohammad Agus Prayitno; Ani Rusilowati; Wiwi Isnaeni; Deni Ebit Nugroho (Chemistry Education Department, 2023)
This study aims to develop and produce an instrument for assessing students' communication skills and creativity in the Chempreneurship course. This research is a development research that uses the 4D model. This assessment instrument contains a theoretical description, a lattice of communication and creativity skills assessment instruments and communication and creativity skills assessment sheets that have been validated by experts and tested. The results of this study are a communication skills and creativity research instrument that is feasible to use, valid, and reliable. The instrument is declared fit for use if the results of the expert appraisal test with CVI obtain a score of ≥ 0.8. The results of the expert appraisal test for communication instruments with CVI obtained a score of 0.88 and a creativity instrument of 0.90. The results of the development testing of the communication skills instrument obtained 16 items, which were declared valid and reliable with a reliability value of 0.891. The results of the development testing of the creativity instrument show that all items are declared valid and reliable with a reliability value of 0.854. The result of the development instrument is feasible to measure communication skills and creativity.